Transforming lives: Patricia Ajayi’s journey with farmers outreach - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
As a lecturer in Economics and Management Studies at the University of Ibadan, Patricia Ajayi had always understood the theoretical significance of agriculture. However, her practical perspective was limited—until she attended the training organized by Radio IITA.